2016
DOI: 10.1097/pas.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Two Subtypes of Atypical Leiomyoma

Abstract: Atypical leiomyoma (ALM) is a rare variant of uterine smooth muscle tumors. Several recent studies have suggested that ALM has distinct, but also heterogeneous, histologic and molecular features, yet little is known about the biology and histogenesis of ALM. Some have even postulated whether the atypical histologic features represent true atypia or simply degenerative changes. In this study, we analyzed the cytologic features of 60 ALM cases and found that ALM could be further divided into two subtypes, type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…Furthermore, we expanded on previous observations and demonstrated that leiomyomas with bizarre nuclei with an aberrant FH/2SC immunoprofile are genetically distinct from those with a normal FH/2SC staining pattern, with somatic FH genetic alteration restricted to the former and TP53 and/or RB1 alterations significantly more frequent in the latter. The concept of two subtypes of leiomyomas with bizarre nuclei has also been recently described by Ubago et al 39 in which their type I atypical leiomyomas were more likely to show “hereditary leiomyomatosis and renal cell carcinoma syndrome features,” whereas type II atypical leiomyomas had a higher rate of TP53 and MED12 mutations. It should be noted that one of the cases harboring a somatic FH missense mutation coupled with loss of the wild-type allele (SCU14T) retained FH expression while also being 2SC-positive.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, we expanded on previous observations and demonstrated that leiomyomas with bizarre nuclei with an aberrant FH/2SC immunoprofile are genetically distinct from those with a normal FH/2SC staining pattern, with somatic FH genetic alteration restricted to the former and TP53 and/or RB1 alterations significantly more frequent in the latter. The concept of two subtypes of leiomyomas with bizarre nuclei has also been recently described by Ubago et al 39 in which their type I atypical leiomyomas were more likely to show “hereditary leiomyomatosis and renal cell carcinoma syndrome features,” whereas type II atypical leiomyomas had a higher rate of TP53 and MED12 mutations. It should be noted that one of the cases harboring a somatic FH missense mutation coupled with loss of the wild-type allele (SCU14T) retained FH expression while also being 2SC-positive.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies have identified that these features can also be seen in sporadic leiomyomas. 35 39 In a morphological-based study by Alsolami et al, 35 six pathologists evaluated a series of 30 uterine leiomyomas (19 from patients with germline-proven hereditary leiomyomatosis and renal cell carcinoma syndrome and 11 sporadic) for the above described features; however, interobserver variability was poor for most parameters. Another study observed at least one of these morphologic findings in 92% (11/12) of uterine leiomyomas from non-hereditary leiomyomatosis and renal cell carcinoma syndrome patients, but for their two leiomyomas from patients with germline-proven mutations, only one showed all of the “hereditary leiomyomatosis and renal cell carcinoma syndrome features”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those cases with mixed type I and II nuclear features, we defined cases as either type I or II when over 70% of the tumor cells appeared to show nuclear features favoring one or another. The detailed description of type I and II characterization has been outlined in a previous study 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Historically, many sporadic SMT-FH were diagnosed as LM-BN due to the significant nuclear atypia 11, 12 . LM-BN also present with a wide range of histologic features 1, 3, 4 and in our set of tumors originally diagnosed as LM-BN, nearly half showed nuclear features similar to SMT-FH 9, 10 and we therefore defined them as type I LM-BN 13 . This suggests that many uterine smooth muscle tumors with atypical histology diagnosed as LM-BN may be related to FH alterations/mutations.…”
Section: Introductionmentioning
confidence: 98%